2015
DOI: 10.1097/ajp.0000000000000086
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Pilot Multicenter Genotype-based Randomized Placebo-controlled Trial of Propranolol to Reduce Pain After Major Thermal Burn Injury

Abstract: Background Results of previous studies suggest that β-adrenoreceptor activation may augment pain, and that β-adrenoreceptor antagonists may be effective in reducing pain, particularly in individuals not homozygous for the catechol-O-methyltransferase (COMT) high activity haplotype. Methods Consenting patients admitted for thermal burn injury at participating burn centers were genotyped; those who were not high activity COMT homozygotes were randomized to propranolol 240mg/day or placebo. Primary outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…49 Published studies of analgesics, electromagnetic therapy, and acupuncture to reduce persistent pain after MVC are too small to be conclusive. 50-52 Teaching pain coping skills, 53,54 treatment with novel therapeutic agents, 55,56 or using cognitive behavioral therapy to reduce depressive or pain catastrophizing symptoms 10 may have utility in this population. More work is needed to develop and test interventions such as these in the vulnerable and growing population of older adults experiencing MVC.…”
Section: Discussionmentioning
confidence: 99%
“…49 Published studies of analgesics, electromagnetic therapy, and acupuncture to reduce persistent pain after MVC are too small to be conclusive. 50-52 Teaching pain coping skills, 53,54 treatment with novel therapeutic agents, 55,56 or using cognitive behavioral therapy to reduce depressive or pain catastrophizing symptoms 10 may have utility in this population. More work is needed to develop and test interventions such as these in the vulnerable and growing population of older adults experiencing MVC.…”
Section: Discussionmentioning
confidence: 99%
“…9,24,25 The latest meta-analysis 9 included eight studies in quantitative synthesis and indicated that there were no differences in mortality or sepsis, while the use of propranolol in burned patients resulted in lower values of HR. As a few new RCTs [10][11][12][13][14][15][16][17][18][19][20][21] have been reported recently, we conducted this systematic review and metaanalysis to evaluate the effectiveness and safety of beta blocker in burned patients. We further confirmed that the use of beta antagonist in burned patients has no significant effect on sepsis and mortality and reduced HR.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current research results, early identification and control of psychological problems such as anxiety or depression helps accelerate the process of wound healing. 32,33 Orrey et al 10,18,19 used the PSS-I criteria 34 to determine PTSD, while ASD was measured by the "acute stress disorder symptom checklist." 35 Our results have shown that the occurrence of stress events such as PTSD and ASD in propranolol-treated group after burns is lower than control (RD = −0.01), but this result is not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations